2002
DOI: 10.1590/s0004-28032002000300005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e prognóstico da peritonite bacteriana espontânea: experiência em pacientes internados em um hospital geral de Porto Alegre, RS, Brasil (1991-2000)

Abstract: RESUMO -Racional -A peritonite bacteriana espontânea é complicação freqüente nos pacientes com cirrose e ascite, apresentando taxa de recurrência em 1 ano próxima de 70%. Objetivos -Avaliar a prevalência da peritonite bacteriana espontânea em pacientes com ascite por hepatopatia crônica e o impacto da sua presença na sobrevida dos mesmos. INTRODUÇÃOEstudos demonstram que 30% a 50% dos cirróticos apresentam infecções bacterianas na admissão hospitalar ou a desenvolvem durante a mesma (5,40) . Estas são respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
(69 reference statements)
1
6
0
Order By: Relevance
“…The incidence of SBP in this sample was 11% and is similar to other Brazilian studies [7,21,22]. The low incidence of such infection could be explained by the fact that most of the ascitic fluid samples were collected in the outpatient setting and is in accordance with the incidence reported in the literature for this population [7,22].…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of SBP in this sample was 11% and is similar to other Brazilian studies [7,21,22]. The low incidence of such infection could be explained by the fact that most of the ascitic fluid samples were collected in the outpatient setting and is in accordance with the incidence reported in the literature for this population [7,22].…”
Section: Discussionsupporting
confidence: 89%
“…Ascitic fluid should be cultured at bedside in blood culture bottles, as soon as the paracentesis is done, as firstly demonstrated by Runyon and colleagues (1987) in order to achieve a positive result in almost 91% of the samples. Although many studies have confirmed Runyon’s results, Brazilian studies could not reach this accuracy in isolating SBP pathogens (Sette et al 1986; Mattos 1994; Figueiredo et al 1999; Coral et al 2002). In our studied group of patients, ascitic fluid culture was positive in only 28.5% of samples although it has been cultured at bedside and in accordance to previously described standard techniques.…”
Section: Diagnosismentioning
confidence: 97%
“…First of all, the results of culture are not readily available, which postpones the diagnosis and treatment of the infection. Secondly, one of the most frequent variants of ascitic fluid infection is culture-negative neutro-cytic ascites, which occurs in approximately 30% to 50% of patients (Sette et al 1986; Runyon et al 1987; Figueiredo et al 1999; Coral et al 2002). …”
Section: Diagnosismentioning
confidence: 99%
“…Cirrhotic patients are more likely to develop bacterial infections and spontaneous bacterial peritonitis (SBP), which is the most frequent and potentially lethal complication of ascites [ 1 3 ]. The prevalence of SBP in cirrhotic patients is 10–30% in hospitalized patients [ 1 , 3 , 4 ] and has a yearly recurrence rate close to 70% [ 5 ]. SBP is associated with high mortality and the probability of long-term survival is 25–50% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately two-thirds of SBP cases are asymptomatic [ 1 ]; thus the protocols of clinical practice set forth by the American Association for the Study of Liver Disease and EASL recommend performing analysis of ascites fluid for diagnosis of infection after each paracentesis procedure [ 7 ]. However, this approach is debatable and there are few studies that evaluate the analysis of ascitic fluid in asymptomatic patients [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%